Managing Tahsin and Tahfiz Learning in Public Schools - Achadi Budi Santosa (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2022)
The existence of reading the Quran learning in school is one of the Muslim student's parent's wishes. However, the existing phenomenon shows that many schools cannot allocate sufficient time for this learning. This study seeks to reveal the management of learning tahsin and tahfizul Quran in public schools. This study used a qualitative method, in-depth interview techniques, field observations, and document reviews. Participants consisted of school principals, deputy principals, ustaz, tahfiz, and tahsin program coordinators, and 11 students. Results of the study showed that the management of tahsin and tahfiz learning was carried out by optimizing management functions that were supported by the leadership of competent principals and ustaz so that most Muslim students are finally able to read the Quran well. Some of them are even able to memorize the thirtieth juz. The results of this study indicate the importance of consistent management in tahsin learning, the lack of seriousness in management results in low learning effectiveness.